Highly Reliable Multiport PUF Circuit Based on MOSFET Zero Temperature Coefficient Point. Issue 4 (1st July 2018) - Li, Gang; Wang, Pengjun; Qian, Haoyu
Abstract : By using processing variations in the unitcircuits of the same structures and design parameters during manufacturing, Physical unclonable function (PUF) generates security keys with characteristic of uniqueness, randomness and unclonability. In this paper, a highly reliable multiport PUF scheme was proposed based on MOSFET Zero temperature coefficient (ZTC) point. It consists of input register, deviation‐current generating module, arbiter array and obfuscation circuit. After reconfiguring deviation‐current generating module by applying different input challenges, the PUF circuit updates keys without physical replacement. And multi‐bit keys can be generated in one clock cycle. In TSMC‐LP 65nm CMOS technology, the layout of 64‐port reconfigurable PUF occupies 131 μmx242μm with custom designing. Experimental results show that the PUF circuit has good statistical characteristic of uniqueness and randomness. It exhibits high reliability of 98.2% with respect to temperature variation from ‐40°C to 125°C and supply voltage variation from 1.08V to 1.32V, indicating that it can be reliably and effectively used in information security field.